Isolation and Characterization of Crab Haemolymph Exosomes and Its Effects on Breast Cancer Cells (4T1) - Rezakhani, Leila; Alizadeh, Morteza; Sharifi, Esmaeel; Soleimannejad, Mostafa; Alizadeh, Akram (Cell journal (Yakhteh), 2021)
The use of animal or plant exosomes in cancer treatment is promising because of their easy access and low cost. Freshwater crabs are used in traditional Iranian medicine to treat cancer. This study aims to determine the anti-cancer properties of exosomes removed from freshwater crabs on a breast cancer cell line (4T1) compared to bone marrow mesenchymal stem cells (BMSCs). In this experimental study, crab haemolymph exosomes were isolated via the precipitation method and characterised by electron microscopy, dynamic light scattering (DLS), and Western blot analysis. The protein concentration and total antioxidant capacity of these exosomes were determined by bicinchoninic acid (BCA) and cupric reducing antioxidant capacity (CUPRAC). The 4T1 cells and BMSCs were treated with exosomes and we assessed the cell survival by the resazurin and MTT assays. The level of nitric oxide (NO) secretion from the 4T1 cells was determined after treatment with the exosomes. Electron microscopy, DLS and Western blot for CD63 confirmed that the isolated exosomes were <100 nm in size and expressed CD63. The total antioxidant capacity in these exosomes was 1.003 μM/ml and the protein concentration was 650 mg/ml. Resazurin and MTT assay results showed a decrease in survival of the 4T1 cells (P≤0.001) after treatment with the exosomes compared to cell growth in the exosome-treated BMSCs. Crab haemolymph contains protein-rich exosomes with antioxidant activities that can have anti-cancer effects on 4T1 cells. These exosomes may be proposed for breast cancer therapeutics.